Handbook of Research on Serious Games as Educational, Business and Research Tools 2012
DOI: 10.4018/978-1-4666-0149-9.ch062
|View full text |Cite
|
Sign up to set email alerts
|

New Forms of Interaction in Serious Games for Rehabilitation

Abstract: This chapter addresses up-to-date research development regarding the adoption of more natural forms of interaction in the Serious Games for Rehabilitation domain of application. The chapter starts by presenting fundamental concepts on Serious Games illustrated by relevant applications. It describes the main problems involved and how Serious Games can benefit the process of rehabilitation. A comprehensive literature survey is presented and accompanied by a proposed set of classification criteria towards a taxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…For example, capturing the lip movements can help in the speech recognition process [13]. An architecture [7] that accommodates the inclusion of several modalities as modules and also some previous studies [6,10] on usability are described in [6,7,10].…”
Section: Natural and Multimodal User Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, capturing the lip movements can help in the speech recognition process [13]. An architecture [7] that accommodates the inclusion of several modalities as modules and also some previous studies [6,10] on usability are described in [6,7,10].…”
Section: Natural and Multimodal User Interfacesmentioning
confidence: 99%
“…Human actions are interpreted by machines as commands that control system operations [26]. This means that humans are able to use the system with very little practice, through natural movements / actions, since these behaviors are deeply rooted in their daily experiments, reducing the cost of system use, time of learning, and time of getting used to the system commands, and making the interaction easier to handle and more intuitive [6,27,28]. The main objective in this approach is to interact with the computer the way we interact with the world [18].…”
Section: Natural and Multimodal User Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their test results showed that the Fourier descriptors and the Manhattan distance-based classifier achieved recognition rates of 95% with small computational latency. In terms of classification and learning, machine learning algorithms have been applied successfully to many fields of research like, face recognition and facial expressions [19,20], automatic recognition of a musical gesture by a computer [21], classification of robotic soccer formations [22], classifying human physical activity from on-body accelerometers [23], automatic road-sign detection [24,25], static hand gesture classification [26], serious games applied to rehabilitation [27][28][29][30] and intelligent wheelchairs [20,[31][32][33][34].…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that most of these patients sometimes get into depression as soon as the rehabilitation program begins, contributing to increase even more the associated healthcare costs. In previous studies [1][2][3][4] we discuss issues and identified features that could benefit the rehabilitation process using Serious Games. Based on that the main objective of this work is to describe our work regarding the design and implementation of an hardware/software architecture for the development of Serious Games in Health Rehabilitation, to augment patients' motivation during their recuperation plan and that integrates the set of features we find as relevant to this process.…”
Section: Introductionmentioning
confidence: 99%